Solid Pseudopapillary Neoplasm of Pancreas In A 35 Year Old Lady - Imdad, Sadia; Saha, Pankaj Kumar; Rahman, Md Mustafizur; Hoque, Md Mozammal; Saha, Krishna Pada; Ahmed, Farhad Uddin; Bin Aziz, Nur Mohammod Sayed (Journal of Shaheed Suhrawardy Medical College, 2018)
Solid pseudopapillary neoplasm of pancreas (SPN) is a rare entity; therefore proper diagnosis, evaluation and formulation of treatment protocols is difficult. The commonest presenting symptom is abdominal pain. This article presents a case of solid pseudopapillary neoplasm of pancreas in a 35 years old lady. A high index of clinical suspicion is necessary to suspect and diagnose SPN. This diagnosis should be borne in mind when young female patients present with a pancreatic mass. J Shaheed Suhrawardy Med Coll, June 2017, Vol.9(1); 31-34